Interleukin-6 and Cyclooxygenase-2 downregulation by fatty-acid fractions of Ranunculus constantinopolitanus - Al-Saghir Jamal A; Homaidan Fadia R; Ezzeddine Rima A; Fostok Sabreen F; Salloum Ralph G; Saliba Najat A; Talhouk Rabih S (BMC, 2009)
Abstract Background Medicinal plants represent alternative means for the treatment of several chronic diseases, including inflammation. The genus Ranunculus, a representative of the Ranunculaceae family, has been reported to possess anti-inflammatory, analgesic, antiviral, antibacterial, antiparasitic and antifungal activities, possibly due to the presence of anemonin and other. Different studies have shown the occurrence of unusual fatty acids (FAs) in Ranunculaceae; however, their therapeutic role has not been investigated. The purpose of this study is to characterize potential anti-inflammatory bioactivities in Ranunculus constantinopolitanus D'Urv., traditionally used in Eastern Mediterranean folk medicine. Methods The aerial part of R. constantinopolitanus was subjected to methanol (MeOH) extraction and solvent fractionation. The bioactive fraction (I.2) was further fractionated using column chromatography, and the biologically active subfraction (Y2+3) was identified using infrared (IR) spectroscopy, nuclear magnetic resonance (NMR) and gas chromatography-mass spectrometry (GC-MS). The effects of I.2 and Y2+3 on cell viability were studied in mouse mammary epithelial SCp2 cells using trypan blue exclusion method. To study the anti-inflammatory activities of I.2 and Y2+3, their ability to reduce interleukin (IL)-6 levels was assessed in endotoxin (ET)-stimulated SCp2 cells using enzyme-linked immunosorbent assay (ELISA). In addition, the ability of Y2+3 to reduce cyclooxygenase (COX)-2 expression was studied in IL-1-treated mouse intestinal epithelial Mode-K cells via western blotting. Data were analyzed by one-way analysis of variance (ANOVA), Student-Newman-Keuls (SNK), Tukey HSD, two-sample t-test and Dunnett t-tests for multiple comparisons. Results The chloroform fraction (I.2) derived from crude MeOH extract of the plant, in addition to Y2+3, a FA mix isolated from this fraction and containing palmitic acid, C18:2 and C18:1 isomers and stearic acid (1:5:8:1 ratio), reduced ET-induced IL-6 levels in SCp2 cells without affecting cell viability or morphology. When compared to fish oil, conjugated linoleic acid (CLA) and to individual FAs as palmitic, linoleic, oleic and stearic acid or to a mix of these FAs (1:5:8:1 ratio), Y2+3 exhibited higher potency in reducing ET-induced IL-6 levels within a shorter period of time. Y2+3 also reduced COX-2 expression in IL-1-treated Mode-K cells. Conclusion Our studies demonstrate the existence of potential anti-inflammatory bioactivities in R. constantinopolitanus and attribute them to a FA mix in this plant.